Pengaruh Stress Kerja Terhadap Perilaku Produktif Ditinjau dari Pemberian Kompensasi yang Standar - Nazilatur Rochmawati; M. Wardianto (Ilmu Psikologi Universitas Yudharta Pasuruan, 2020)
Employee work productivity is the main thing in maintaining and even improving the quality and strength of the company. This is a challenge that is not easy for employees. One aspect that is often discussed with this variable is the level at which employees work. The purpose of this study was to determine the relationship between work stress and productive relationships at PT. Uniplastindo Interbuana, Pasuruan. The results showed that the hypothesis stating there was a relationship between work stress and productifity was rejected at the 5% significance level, where the rxy of -0.203 <r table 5% of 0.279. Thus the level of work stress of employees is not a significant factor for predicting the level of productivity of competition.